ANALISIS MOTIVASI KERJA TERHADAP KINERJA PEGAWAI KECAMATAN DI KOTA BOGOR - Hari Muharam (MAGMA : JURNAL MAGISTER MANAJEMEN, 2014)
The purpose of this study, is to describe and to analyze the motivation of employees working at the District Office of Central Bogor.The study population was all employees in Central Bogor subdistrict with a population of about 125 employees staff sections villages in Central Bogor subdistrict with research samples totaling 95 employees people using Slovin. The research instrument was a questionnaire. Collected data is processed by using correlation analysis technique.The results showed that: There is a positive relationship between work motivation and employee performance is weak with employee performance with correlation coefficient of 0.395. While the coefficient of determination obtained 15.8%Keywords: Work Motivation and Employee Performance